R2(GFR)CHADS2 and R2(GFR)CHA2DS2VASc schemes improved the performance of CHADS2 and CHA2DS2VASc scores in death risk stratification of Chinese older patients with atrial fibrillation - Fu S (Dove Medical Press, 2017)
Shihui Fu,1,2,* Shanjing Zhou,3,* Leiming Luo,1 Ping Ye1 1Department of Geriatric Cardiology, 2Department of Cardiology and Hainan Branch, 3Department of Traditional Chinese Medicine and Hainan Branch, Chinese People’s Liberation Army General Hospital, Beijing, People’s Republic of China *These authors contributed equally to this work Background: This analysis was carried out to refine the CHADS2 and CHA2DS2VASc scores by combining creatinine clearance (CrCl) and glomerular filtration rate (GFR) and evaluate the performance of CrCl-based and GFR-based schemes in death risk stratification of Chinese older patients with atrial fibrillation (AF).Methods: There were 219 older patients with AF, and all-cause mortality was assessed during the follow-up of 1.11 years. Renal function was evaluated using the CrCl formula and different GFR (Modification of Diet in Renal Disease [MDRD], Chinese MDRD [CMDRD], Mayo Clinic Quadratic [Mayo] and Chronic Kidney Disease Epidemiology Collaboration [CKD-EPI]) formulas, and five kinds of R2CHADS2 and R2CHA2DS2VASc schemes were generated by combining CrCl and GFR with CHADS2 and CHA2DS2VASc scores.Results: In Cox regression multivariate analysis, CrCl <60 mL/min was moderately associated with death risk (P=0.122 and P=0.144). When MDRD, CMDRD, CKD-EPI and Mayo formulas were used to ascertain the GFR, GFR <60 mL/min/1.73 m2 was significantly associated with death risk (P<0.001 for all). In the models with CHADS2 and CHA2DS2VASc scores as the linear covariates, CrCl and GFR as the continuous variables were significantly associated with death risk (P<0.05 for all). C-statistics of CrCl-based schemes – R2(CrCl)CHADS2 and R2(CrCl)CHA2DS2VASc – moderately exceeded that of CHADS2 and CHA2DS2VASc scores (P=0.081 and 0.082). C-statistics of GFR-based schemes – R2(GFR)CHADS2 and R2(GFR)CHA2DS2VASc – significantly exceeded that of CHADS2 and CHA2DS2VASc scores (P<0.05 for all).Conclusion: Chinese older patients with AF with lower levels of GFR and GFR <60 mL/min/1.73 m2 had a significantly high death risk, and those with lower levels of CrCl or CrCl <60 mL/min had a significantly or modestly high death risk. There was significantly better performance of GFR-based schemes and moderately better performance of CrCl-based schemes in death risk stratification compared with CHADS2 and CHA2DS2VASc scores. Keywords: atrial fibrillation, CHADS2, CHA2DS2VASc, older patients, creatinine clearance, glomerular filtration rate